Structure-activity relationship of trifluoromethyl-containing metallocenes: electrochemistry, lipophilicity, cytotoxicity, and ROS production - Maschke, Marcus; Alborzinia, Hamed; Lieb, Max; Wölfl, Stefan; Metzler-Nolte, Nils (ChemMedChem, 2014)
Abstract We report the synthesis of trifluoromethylated metallocenes (M=Fe, Ru) and related metal-free compounds for comparison of their biological properties with the aim to establish structure?activity relationships toward the anti-proliferative activity of this compound class. All new compounds were comprehensively characterized by NMR spectroscopy (1H, 13C, 19F), mass spectrometry, IR spectroscopy, and elemental analysis. A single-crystal X-ray structure was obtained on the Ru derivative, 1-(1-hydroxy-1-hexafluoromethylethyl)ruthenocene (3). The cytotoxicity of all compounds was tested on MCF-7, HT-29, and PT-45 cells, and IC50 values as low as 12??M were observed. Both the metallocene moiety and the hydroxy function are crucial for cytotoxicity. In addition, the activity decreased sharply even if only one trifluoromethyl group was replaced with a methyl group. Electrochemical investigations by cyclic voltammetry revealed that all CF3-containing compounds are harder to oxidize than the unsubstituted metallocenes. Moreover, log?P determination by RP-HPLC showed the fluorinated derivatives to have higher lipophilicity, with log?P values up to 4.6. At the same time, the generation of reactive oxygen species (ROS) in Jurkat cells by these compounds was investigated by flow cytometry. Strong ROS production was shown exclusively for the bis-CF3 derivative 1-(1-hydroxy-1-hexafluoromethylethyl)ferrocene (1) after 6 and 24?h. Also on the Jurkat cell line, only compound 1 strongly induces necrosis after 24 and 48?h, as shown by annexin?V/propidium iodide staining. No induction of apoptosis was observed. We propose that compound 1 is more efficiently incorporated into cancer cells relative to all other derivatives, causing significant induction of oxidative stress within the cell, which ultimately leads to cell death.
Gesehen am 14.08.2020